2017
DOI: 10.1002/ijgo.12168
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol use for second‐trimester termination of pregnancy among women with one or more previous cesarean deliveries

Abstract: Misoprostol was safe for second-trimester termination among women with previous cesareans; however, the efficacy of the local regimen was reduced owing to high placental retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…Studies have shown that the main complications of using misoprostol in women with previous history of cesarean section include uterine rupture, need for blood transfusion, retained placenta and surgical evacuation of the uterus, lack of response to treatment and the need for auxiliary treatment for pregnancy termination and hysterectomy. Among these complications, uterine rupture is the most dangerous and serious complication [14,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the main complications of using misoprostol in women with previous history of cesarean section include uterine rupture, need for blood transfusion, retained placenta and surgical evacuation of the uterus, lack of response to treatment and the need for auxiliary treatment for pregnancy termination and hysterectomy. Among these complications, uterine rupture is the most dangerous and serious complication [14,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The participants were divided into 3 groups based on their history of cesarean sections: without a history of cesarean section, with a history of one cesarean section and with a history of more than one cesarean sections and uterine scaring (any history of uterine surgery such as cesarean and myomectomy). The divided dose of misoprostol in all cases ranged from 100 to 400 µg, at intervals of 4 to 6 hours, via vaginal administration [12][13][14].…”
Section: Study Protocolmentioning
confidence: 99%
“…The most important reason for this is the increased risk of uterine rupture, placental retention and postpartum bleeding associated with them in the presence of a history of cesarean section. 3,[6][7][8][9][10] Therefore, with increasing cesarean rates, the management of pregnancy terminations is becoming an important problem. 2,11 From past to present, many studies using misoprostol for pregnancy termination in patients with previous cesarean section (C/S) have been presented.…”
Section: Introductionmentioning
confidence: 99%
“…2,11 From past to present, many studies using misoprostol for pregnancy termination in patients with previous cesarean section (C/S) have been presented. 3,[6][7][8][9][10][11][12] The misoprostol dose, route, dose ranges and gestational week limits used in these studies vary. This situation prevents reaching a certain standardization in management in patients planned for ToP, whether or not they have a history of C/S.…”
Section: Introductionmentioning
confidence: 99%
“…The dosage of misoprostol often varies depending on gestation and presence of prior uterine scar (Figure Royal Women's Hospital mifepristone and misoprostol regimen). Although there is strong evidence for the time efficacy of mifepristone and misoprostol in combination, including specifically for MTOP for fetal anomaly ≥20 weeks' gestation, 3–5 there is lack of consensus regarding the preferred timing, route and dosage, especially in the context of a uterine scar 6,7 . Postnatal investigations offered include postmortem examination, placental histopathology and chromosomal analysis (if not performed prenatally).…”
Section: Introductionmentioning
confidence: 99%